Pesan Moral dalam Film KKN di Desa Penari: Analisis Semiotika Roland Barthes - Nur Laila; Ahmad Zulfikar Ali (Bayan lin-Naas : Jurnal Dakwah Islam, 2026)
With increasingly sophisticated technology and the ability to present everything, it has led to moral decline. Without us realizing it, a moral crisis is currently affecting young people, especially teenagers, in this era. One effort to prevent this moral decline is utilizing mass communication media in the form of film. One such film, "KKN Di Desa Penari," focuses on the moral message conveyed in the film. The researcher used a media text analysis approach with a qualitative descriptive approach, incorporating Roland Barthes' semiotic analysis, which has three meanings: denotation, connotation, and metalanguage or myth. The researcher used observation and data validation methods using diligent observation and triangulation. The results of this study indicate that sixteen of the seventy scenes in the film "KKN Di Desa Penari" contain moral messages. The research findings reveal that the relationship between humans and God, the relationship between humans and other humans as social beings, and the relationship between humans and themselves are related.